(untitled) (Castilla. Estudios de Literatura, 2016)
In this article, the first three works of José Martínez Ruiz, Azorín (1873-1967), will be analyzed. La crítica literaria en España (1893), Moratín (1893) and Buscapiés (1894) will be studied according to two objectives. The first and main objective consists in determining what kind of literary personality Azorín wanted to build for himself in his three first books. For this purpose, the theory of “la voluntad de estilo” (the will for style) exposed by Juan Marichal in his book Teoría e historia del ensayismo hispánico (1984) will be used as the main methodological principle. Secondly, it will be verified if it is true or not that the young Azorín used the anarchist ideology to build his public image as a writer. In conclusion, it will be postulated that the young Martínez Ruiz was involved, during the period of 1893-1894, in a stage of learning in which he pretended to show an image of himself as a Crítico Satírico or Crítico Discordante. In addition, it will be clarified that Azorín had not used until this moment the anarchism as his aesthetic and ideological support.